Sustainable democracy and political domination : a rotational presidency among Nigerian ethnic groups / Abdul Rauf Ambali and Ahmed Letswa Mohammed - Ambali, Abdul Rauf; Mohammed, Ahmed Letswa (Universiti Teknologi MARA, Shah Alam, 2016)
This work discusses rotational presidency and its challenges to sustainable democracy in Nigeria. It focuses on its workability in a highly ethnically pluralised and heterogeneous society like Nigeria that is characterised by competition for national resources either in terms of technocratic or political offices. It contends that the cliché is born out of elite struggle for share of national cake via capturing power at the centre where primitive accumulation takes place. Rotational presidency hence lacks democratic correlates. It argues that Nigeria Federal system allows for too much concentration of power and resources at the centre thereby making political competition intense at that level. Methodologically, the paper is based on review of published work, unpublished literature, comments of national commentators as well as observation as students of Nigeria government and politics. The work concludes with a strong recommendation that Nigerians need to jettison a federal arrangement that concentrate power and resources at the centre - the system that allows for hot contestation of presidency among various national ethnic elites to a more workable federal system that would decongest the centre for power tussle and or a different approach based on a different philosophy that will guarantee groups' rights by recognising the heterogeneity of the country's polity.